2016
DOI: 10.1109/jstars.2016.2604577
|View full text |Cite
|
Sign up to set email alerts
|

MODIS Environmental Data to Assess Chikungunya, Dengue, and Zika Diseases Through Aedes (Stegomia) aegypti Oviposition Activity Estimation

Abstract: Aedes aegypti is the main vector for Chikungunya, Dengue, and Zika viruses in Latin America and it represents a main threat for our region. Taking into account this situation, several efforts have been done to use remote sensing to support public health decision making. Moderate resolution imaging spectroradiometer (MODIS) sensor provides moderate-resolution remote sensing products; therefore, we explore the application of MODIS products to vector-borne disease problems in Argentina. We develop temporal foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Vegetation index is one of the most important variables, showing a positive relationship and fluctuating in a similar way as the oviposition activity. This relationship has also been observed between the NDVI and the egg number fluctuation of this species in the north of the country [7]. In addition, studies in La Habana, Cuba, showed a correlation between the number of larva infested containers and the presence of trees and vegetation, which demonstrates the importance of the shade that vegetation provides to containers in which the Ae.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Vegetation index is one of the most important variables, showing a positive relationship and fluctuating in a similar way as the oviposition activity. This relationship has also been observed between the NDVI and the egg number fluctuation of this species in the north of the country [7]. In addition, studies in La Habana, Cuba, showed a correlation between the number of larva infested containers and the presence of trees and vegetation, which demonstrates the importance of the shade that vegetation provides to containers in which the Ae.…”
Section: Discussionsupporting
confidence: 56%
“…Considering the biological characteristics of Ae. aegypti , time lags were applied to the explanatory variables [7, 27], meaning the length of time that has elapsed since the change in weather conditions that is reflected in the response variable in order to obtain a better fitted model.…”
Section: Methodsmentioning
confidence: 99%
“…This study improved previous epidemiology studies, which consider statistical models with linear relationships [47,36,37]. Such improvement is obtained by the use of Machine Learning tools that impose the user no significant additional effort.…”
Section: Discussionmentioning
confidence: 67%
“…Previous experiences on the modeling of epidemiological applications using remotely sensed environmental variables report good results with this approach [51,37,52]. We used simple linear and ridge regressions, the latter with Tikhonov regularization with cross-validation.…”
Section: Linear Regressionsmentioning
confidence: 99%
See 1 more Smart Citation